Treibhaus 5. - Kunstmuseum Düsseldorf (Düsseldorf : Kunstmuseum Düsseldorf, 1990)
von der Bey, Annette ; Damm, Ursula ; Elgin, Dag Erik ; Franke, Manuel ; Geismar, Jarg ; Hohn, Till ; Holtgrewe, Detlef ; Holthöfer, Ulrike ; Kehrwald, Klaus ; Klarner, Susanne ; Mohr, Bertolt ; Schwenk, Martin
Treibhaus 5, Kunstmuseum Düsseldorf, Kunstpalast, 1. Juni bis 22. Juli 1990
boek